2019
DOI: 10.1007/s10461-019-02575-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Moderate the Syndemic Effect of Psychosocial and Structural Factors on HIV Risk Among Young Black Transgender Women and Men who have Sex with Men

Abstract: The interaction between the cumulative effect of psychosocial and structural factors (i.e. syndemic effect) and social networks among young Black transgender women and men who have sex with men (YBTM) remains understudied. A representative cohort of 16-29 year-old YBTM (n=618) was assessed for syndemic factors [i.e. substance use; community violence; depression; poverty; justice system involvement (JSI)], social network characteristics, condomless anal sex (CAS), group sex (GS), and HIV-infection. The syndemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…Among sexual minorities, social support has been found to buffer against the negative effects of homophobic stressors on emotional distress (Doty et al, 2010; Fingerhut, 2018; Wang et al, 2018). Some research has also found that social support related constructs like social capital (i.e., the resources gained through social relationships; Valente et al, 2020) and social network size (Teixeria da Silva et al, 2020) may mitigate the association of stigma (e.g., sex work stigma) with risk behaviors, including CAS. However, the potential buffering effect of perceived social support on CAS in the context of antiretroviral-based HIV prevention has not been directly examined in GBM.…”
Section: Social Support Among Gbmmentioning
confidence: 99%
“…Among sexual minorities, social support has been found to buffer against the negative effects of homophobic stressors on emotional distress (Doty et al, 2010; Fingerhut, 2018; Wang et al, 2018). Some research has also found that social support related constructs like social capital (i.e., the resources gained through social relationships; Valente et al, 2020) and social network size (Teixeria da Silva et al, 2020) may mitigate the association of stigma (e.g., sex work stigma) with risk behaviors, including CAS. However, the potential buffering effect of perceived social support on CAS in the context of antiretroviral-based HIV prevention has not been directly examined in GBM.…”
Section: Social Support Among Gbmmentioning
confidence: 99%
“…Fourth, although quantitative studies have found a combined, or syndemic, effect of negative processes at structural/systemic, interpersonal, and individual on engagement in care among young Black MSM [ 28 , 36 ], this is one of the first qualitative studies [ 37 ] to explore how and ways in which these influences affect each other. For example, for some participants, housing instability and/or taking a break from school led to depression and disruptions in one’s daily schedule, both of which led to lowered motivation and capacity to remain engaged in care.…”
Section: Discussionmentioning
confidence: 99%
“…In health behavior, syndemics are linked to health problems that occur among specific groups because of personal (eg, higher anxiety or depression) or environmental conditions (eg, disease concentration and lack of resources) that interact and produce negative effects on individuals [21]. A large body of research on YMSM uses a syndemic framework to understand the health and social inequalities affecting them, as well as the increased sexual and risk-taking behaviors that are usually associated with these disparities [22][23][24][25][26]. The current findings show that enhancing assets and resources that promote resilience and reduce environmental barriers may reduce risk factors and increase the uptake of HIV prevention services.…”
Section: Theoretical Foundation: Positive Youth Development and Resil...mentioning
confidence: 99%